The role of inflammation in age-related macular degeneration - Diana Florina Tricorache; Ana Maria Dascalu; Crenguta Serboiu; Anca Bobirca; Dragos Cretoiu; Dan Bratu; Corneliu Tudor; Laura Carina Tribus (Journal of Mind and Medical Sciences)
Age-related macular degeneration (AMD) is a complex, chronic, and progressive disease which affects the macular area, being one of the leading causes of irreversible vision loss worldwide. Specific alterations of retinal structure occur at the macular level, which regarding its severity can range from the presence of drusen to the development of geographic atrophy or choroidal neovascularization. AMD has long been considered a degenerative disease, but new studies highlight the role of inflammation present both in the atrophic form and in the exudative form. The present review is based on comprehensive research on PubMed and Web of Science databases, and it aims to describe the inflammatory pathways involved in AMD onset and progression. Understanding the molecules involved in AMD pathogenesis, and their mechanism of action, is crucial because they can be both biomarkers with a predictive role in disease management, as well as potential therapeutic targets.